S90 Assessing regional lung ventilation in patients and healthy volunteers using 19F-MRI of inhaled perfluoropropane. (December 2018) - Pippard, B; Neal, M; Maunder, A; Forrest, I; Sabroe, I; Lawson, R; Simpson, AJ; Wild, J; Thelwall, P
Abstract : Introduction: Pulmonary imaging with conventional MRI remains challenging, owing to the low proton density of lung tissue. The use of hyperpolarized gases (e.g. 3 He and 129 Xe) enables assessment of ventilation properties without recourse to ionizing radiation; yet, the requirement for specialized equipment and expertise has largely restricted this technique to research settings. Recently, 19 F-MRI of inhaled perfluoropropane (PFP) has emerged as a viable approach to ventilation imaging in humans, 1 2 offering an alternative to hyperpolarization with potential for translation to clinical practice. Aim: We assessed the utility of 19 F-MRI of inhaled PFP to distinguish ventilation properties in healthy volunteers and patients with respiratory disease. Methods: 28 healthy volunteers (16 M, 12 F; aged 23–61), 2 patients with asthma (1 M, aged 43; 1F, aged 59) and 2 patients with COPD (2F, aged 66 and 76) provided written informed consent and were screened for study eligibility across two UK study sites. Participants underwent a single MRI session on a 3T scanner, involving periodic inhalation of a 79% PFP/21% oxygen gas mixture on up to four occasions. Inhalation sessions typically comprised 3 deep breaths of the gas followed by a breath-hold, during which 19 F-MR images were acquired. Heart rate and oxygen saturations were monitored throughout. Results: A total of 126 inhalation sessions were performed across all participants. The gas mixture was well tolerated, with no adverse events relating to gas inhalation. Homogeneous gas distribution was seen throughout the lungs of healthy volunteers (figure 1a). In contrast, patients with asthma (1b) and COPD (1c) showed heterogeneous gas distribution, reflecting impaired regional ventilation. Conclusions: We have demonstrated the ability to assess regional ventilation properties in healthy volunteers and patients with respiratory disease by 19 F-MRI of inhaled PFP gas. Crucially, this technique can be implemented on MRI scanners with considerably less additional hardware compared to hyperpolarized gas MRI. Future work will determine the reproducibility of this technique to quantify ventilation defects in patients with asthma and COPD, including response to bronchodilator therapy. References: Halaweish AF, et al. Chest2013;144:1300–1310. Gutberlet M, et al. Radiology2018;286:1040–1051.